Development, Practice Patterns, and Early Clinical Outcomes of a Multidisciplinary Liver Cancer Clinic. (21st April 2021) - Jia, Angela Y.; Popovic, Aleksandra; Mohan, Aditya A.; Zorzi, Jane; Griffith, Paige; Kim, Amy K.; Anders, Robert A.; Burkhart, Richard A.; Lafaro, Kelly; Georgiades, Christos; Azad, Nilofer S.; Liddell, Robert P.; et al.
Multidisciplinary care has been associated with improved survival in patients with primary liver cancers. We report the practice patterns and real world clinical outcomes for patients presenting to the Johns Hopkins Hospital (JHH) multidisciplinary liver clinic (MDLC). We analyzed hepatocellular carcinoma (HCC, n = 100) and biliary tract cancer (BTC, n = 76) patients evaluated at the JHH MDLC in 2019. We describe the conduct of the clinic, consensus decisions for patient management based on stage categories, and describe treatment approaches and outcomes based on these categories. We describe subclassification of BCLC stage C into 2 parts, and subclassification of cholangiocarcinoma into 4 stages. A treatment consensus was finalized on the day of MDLC for the majority of patients (89% in HCC, 87% in BTC), with high adherence to MDLC recommendations (91% in HCC, 100% in BTC). Among patients presenting for a second opinion regarding management, 28% of HCC and 31% of BTC patients were given new therapeutic recommendations. For HCC patients, at a median follow up of 11.7 months (0.7-19.4 months), median OS was not reached in BCLC A and B patients. In BTC patients, at a median follow up of 14.2 months (0.9-21.1 months) the median OS was not reached in patients with resectable or borderline resectable disease, and was 11.9 months in patients with unresectable or metastatic disease. Coordinated expert multidisciplinary care is feasible for primary liver cancers with high adherence to recommendations and a change in treatment for a sizeable minority of patients.